A New Approach to Extraction Transformation Loading Using Pipelining (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Companies have lots of precious data lying around  throughout their networks that needs to be moved  from one place to another such as from one business  centre to another or to a data warehouse for  analysis. The problem is that the data lies in  different sorts of heterogeneous systems, and  therefore in all sorts of formats. To accumulate  data at one place and to make strategic decisions  we need a data warehouse system. This consists of  extract, transform and load (ETL) software, which  extract data from various resources, transform it into  new data formats according to required information  needs, and then load it into desired data structure(s).  Such softwares take enormous time for the purpose.  To deal with the problem of time taken by ETL  process, in this paper we are presenting a new  technique of ETL using pipelining. We had divided  ETL process into various segments which worked  simultaneously using pipelining.
Keywords: Data Warehouse; Data Mart; Pipelining; Nested Pipelining